Investigation of Relation between Fracture Scale and Acoustic Emission Time-Frequency Parameters in Rocks - Junwen Zhang (Shock and Vibration)
To investigate relation between fracture scale and acoustic emission time-frequency parameters in rocks, experiments of acoustic emission monitoring of granite uniaxial compression were carried out. The AE signal energy and dominant-frequency of granite fracture process were extracted by means of AE time-frequency analysis. The relation between fracture scale and AE time-frequency parameters (energy and frequency) in granite fracture process was analyzed. The evaluation model of rock fracture scale based on AE energy and dominant-frequency was established by using the intrinsic relation between the scale of rock fracture and the time-frequency parameters of rock mass. The evolution of crack scale in the process of uniaxial compression was analyzed based on the evaluation model of rock fracture scale. Results show that the AE energy and the dominant-frequency can reflect the crack scale inside the rock. The scale of rock fracture is proportional to the AE energy, which is inversely proportional to the AE dominant-frequency. Signals with low frequency and high energy usually represent large-scale cracks. On the contrary, if the high frequency has low energy value, it indicates a small-scale crack. The theory and method of evaluation of rock rupture scale based on AE time-frequency information (energy, frequency) can describe the failure process of rock crack scale variation characteristics. It provides a way and method for investigating the characterization of fracture size evolution process of rock fracture.